2006
DOI: 10.1097/01.sap.0000194245.94684.54
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Midcarpal Arthrodesis in the Treatment of Scaphoid Nonunion Advanced Collapse (SNAC-Wrist) and Scapholunate Advanced Collapse (SLAC-Wrist)

Abstract: Our data demonstrate that midcarpal arthrodesis is a reliable procedure for treating SLAC- and SNAC-wrists in stages II and III and, furthermore, one which preserves some range of motion. Total wrist fusion should only be used in exceptional circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 35 publications
(32 reference statements)
2
40
1
Order By: Relevance
“…11 Singlecolumn fusion also requires less amount of graft, reduces operating time, and is generally perceived as a less technically demanding surgery. 4,11 The authors acknowledge some weaknesses of the present study such as being a cadaveric study in which only specific positions and the limited number of specimens that were analyzed. Also, advanced-stage wrist collapse was not present in our study sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Singlecolumn fusion also requires less amount of graft, reduces operating time, and is generally perceived as a less technically demanding surgery. 4,11 The authors acknowledge some weaknesses of the present study such as being a cadaveric study in which only specific positions and the limited number of specimens that were analyzed. Also, advanced-stage wrist collapse was not present in our study sample.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was introduced over two decades ago and is currently the gold-standard treatment for reconstruction 17 because of its high reported success rate. [4][5][6] The four-corner arthrodesis was not biomechanically tested for comparison in the present study. There is currently no consensus regarding the "center of rotation" of the wrist; however, most authors agree that if one exists, it will be found in the head of the capitate, for both palmar-dorsiflexion and radial-ulnar deviation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, scaphocapitate arthrodesis is rarely used to treat arthritis, but rather to provide a functional result similar to treatment options for STT arthritis, allowing for its use in the reduction of the SL interval and for offloading the lunate in the treatment of Kienbock disease (19,20). Scaphoid excision with four-corner fusion can be used in treating scapholunate advanced collapse (SLAC) or scaphoid nonunion advanced collapse (SNAC) (21,22).…”
Section: Midcarpal Arthrodesismentioning
confidence: 99%